Farmers’ Perception of The Role of Farmer Groups in Jambu Village, Lenteng Sub-District, Sumenep District - Kholifah, Aisyah Nur; Widodo, Slamet; Destiarni, Resti Prastika; Subari, Slamet (Jurnal Penyuluhan Pertanian, 2023)
In Jambu Village, 12 farmer groups were formed to improve farmers' knowledge and skills. This study aimed to determine farmers' perceptions of the role of farmer groups in Jambu Village, Lenteng Sub-district, Sumenep District. This research was conducted from November 2022 - January 2023. The number of samples used was 57 farmers from 2 farmer groups selected by purposive and census. The analytical method used is descriptive with a Likert scale to measure farmers’ perception level. The results of the analysis showed that the role of farmer groups as learning classes, vehicles for cooperation, and production units was overall quite good with the role of learning classes being the highest and the role as a production unit being low. So it is necessary to optimize the role of farmer groups as production units by conducting group business activities.